Can angiogenesis inhibitor therapy cause changes in imaging features of hepatic hemangioma- Initial study - Liu, Tang; Pan, Wenxue; Lai, Shengyuan; Luo, Jiawen (Frontiers in Oncology, 2023)
Background To observe whether anti-angiogenesis therapy can induce changes in size and enhancement characteristics of hepatic hemangioma. Method 133 patients with hepatic hemangioma lesions were analyzed and classified into a Bevacizumab group (n=65) and the control group (n=68). The parameters (Volume, CT enhancement ratio, enhancement patterns) of pre-and post-treatment in the bevacizumab and control groups independently calculated and compared by two radiologists. Correlation among the systolic blood pressure, diastolic blood pressure, heart rate with the hemangioma volume was evaluated using Pearson’s correlation analysis. Results The hepatic hemangioma volume was significantly decreased after treatment in the Bevacizumab group (8.6 ± 18.7mL vs.7.3 ± 16.3mL, P<0.05), and there was no significant change in the control group (15.1 ± 19.8mL vs.15.4 ± 20.7mL, P = 0.504). A significant difference in enhancement patterns of hepatic hemangiomas was observed after treatment with Bevacizumab (P<0.01). There was no significant difference in arterial phase (AP)enhancement rate and arterial phase-portal venous phase (AP-PVP) enhancement ratios after treatment in the Bevacizumab and control groups (Ps>0.05).The Pearson correlation results showed that blood pressure, heart rate, and hemangioma volume were unrelated or weakly related before and after bevacizumab treatment under the control of factors including weight, contrast injection scheme and CT scanning scheme. Conclusions Anti-angiogenesis therapy can cause changes in enhancement pattern and volume of hepatic hemangioma. Radiologists should pay more attention to the reexamination of tumor patients treated with anti-angiogenesis therapy.